A PET-based turn-on fluorescent probe for sensitive detection of thiols and H2S and its bioimaging application in living cells, tissues and zebrafish. (28th January 2019) - Xu, Kaixin; He, Longwei; Yang, Yunzhen; Lin, Weiying
Abstract : A two-photon turn-on fluorescent probe regulated by a PET mechanism has been engineered for detection of thiols and H2 S in living cells, tissues and zebrafish. Abstract : A turn-on fluorescent probe, containing a naphthalimide platform and benzothiazole modified by the 2, 4-dinitrobenzenesulfonyl (DNBS) group, was designed as an efficient fluorescent probe for sensitive detection of biological thiols and H2 S species regulated by a photoinduced electron transfer (PET) mechanism. This probe shows a speedy response to analytes and has the ability to detect thiols and H2 S in aqueous and living organisms via an obvious turn-on fluorescence response.